Synthesis of Reduced Graphene Oxide-Modified LiMn0.75Fe0.25PO4 Microspheres by Salt-Assisted Spray Drying for High-Performance Lithium-Ion Batteries - Kim, Myeong-Seong; Kim, Hyun-Kyung; Lee, Suk-Woo; Kim, Dong-Hyun; Ruan, Dianbo; Chung, Kyung Yoon; Lee, Sang Hyun; Roh, Kwang Chul; Kim, Kwang-Bum (NATURE PUBLISHING GROUP, 2016)
Microsized, spherical, three-dimensional (3D) graphene-based composites as electrode materials exhibit improved tap density and electrochemical properties. In this study, we report 3D LiMn0.75Fe0.25PO4/reduced graphene oxide microspheres synthesized by one-step salt-assisted spray drying using a mixed solution containing a precursor salt and graphene oxide and a subsequent heat treatment. During this process, it was found that the type of metal salt used has significant effects on the morphology, phase purity, and electrochemical properties of the synthesized samples. Furthermore, the amount of the chelating agent used also affects the phase purity and electrochemical properties of the samples. The composite exhibited a high tap density (1.1 g cm(-3)) as well as a gravimetric capacity of 161 mA h g(-1) and volumetric capacity of 281 mA h cm(-3) at 0.05 C-rate. It also exhibited excellent rate capability, delivering a discharge capacity of 90 mA h g(-1) at 60 C-rate. Furthermore, the microspheres exhibited high energy efficiency and good cyclability, showing a capacity retention rate of 93% after 1000 cycles at 10 C-rate.
Keywords: CATHODE MATERIAL; STORAGE PROPERTIES; LIFEPO4; NANOPARTICLES; COMPOSITE; SHEETS; RAMAN; SIZE; SPECTROSCOPY; FABRICATION